Single cell S-value calculations of a stochastic cascade model for Auger-electron emitting radionuclides - Vallis, K; Falzone, N; Lee, B; Fernandez-Varea, J; Kibedi, T; Stuchbery, A (Society for Nuclear Medicine, 2016)
Auger-electron (AE) emitting radionuclides could be exploited for therapeutic purposes due to the high local energy deposition by low-energy Auger electrons or may deliver an unintentional mean absorbed dose burden when used as medical imaging agents. Emission spectra of AE emitting radionuclides are essential for dosimetric calculations to quantify the biological damage to the target. The BrIccEmis code, a Monte Carlo model of the Auger cascade is used here to provide radiation spectra data for 14 AE emitting radionuclides. The aim of this study is to compare MIRD single cell Svalues with S-values derived from BrIccEmis generated radiation spectra.